Geographic Variation in the Physical and Mechanical Properties of Dendrocalamus asper Growing on Lombok Island - Syahbana, Ardi; Rini, Dwi Sukma; Lestari, Dini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bamboo is one of the most important non-timber forest products due to its fast growth and excellent mechanical properties. This study aims to assess the impact of growing location on the physical and mechanical properties of Petung bamboo (Dendrocalamus asper) naturally growing on Lombok Island. A total of five bamboo culms were collected from different clumps at three locations, resulting in 15 individual bamboo samples. The tested parameters included moisture content, basic density, tangential and radial shrinkage, modulus of elasticity (MOE), and modulus of rupture (MOR). Data were analyzed using R software (version 4.3.1). The effect of location was examined using a mixed-effects model, where growing location and individual bamboo served as random effects. The results indicate that individual variation has a greater influence on the physical and mechanical properties of D. asper than growing location, with variance components exceeding 50% for moisture content, basic density, MOE, and MOR. These findings suggest that the mechanical and physical properties of D. asper are primarily determined by intrinsic factors rather than environmental conditions. Further research is recommended to investigate additional factors, such as micro-environmental influences on bamboo properties.